Sthiradi Kala Basti-based Ayurveda Management in Duchenne Muscular Dystrophy – A Retrospective Observational Study - Vijay Kumar Pathak; Neha Yadav; Arun Kumar Mahapatra; Prashant Kumar Gupta; Rajagopala Shrikrishna (Journal of Ayurveda)
Introduction:Duchenne muscular dystrophy (DMD) is an X-linked recessive disorder symptom are calf hypertrophy and weakness in proximal muscle in boys. There is no definite cure for this disease and patients are looking to Ayurveda with the hope of a cure. The present study is about determining the therapeutic utility of Panchakarma therapy with Sthiradi Kala Basti and Ayurvedic medicines. Objective: The objective of this study was to study the role of Panchakarma with Sthiradi Kala Basti in the management of DMD. Methods:In this study, data were collected from five patients who underwent Panchakarma-based management in DMD using standardized assessment formats between September 2021 and January 2022. Results:All participants showed improvement in the Barthel Index, three participants showed a decrease and two show an increased value of serum creatine phosphokinase, four participants showed a decrease while one participant showed an increased value of serum creatine kinase-MB, and muscle power increased in all patients. Conclusion:Current treatment shows the effectiveness of Panchakarma-based procedures in improving the clinical features of DMD. No adverse effects of internal medication as well as Panchakarma procedure are reported.